Pertanggungjawaban Hukum Terhadap Warga Negara Asing (WNA) yang Bekerja Tanpa Izin di Indonesia - Shalomoan Shalomoan; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Warmadewa Press, 2024)
This research discusses permits for the use of foreign workers in Indonesia. Regulations that directly discuss labor have been successfully strengthened by the existence of Presidential Regulation No. 20/2018 directly discussing the use of foreign workers. However, in carrying out practical activities, there are still cases of violations of licensing regulations and also the use of foreign workers. The purpose of this study is to review and analyze the legal liability for foreigners working without a permit in Indonesia. The method implemented in conducting this activity is the normative legal research method, where this research will be carried out by the researcher by directly analyzing the literature based on legal materials. The results show that legal liability for foreign workers who work without a valid work permit, will be given sanctions in the form of administrative fines, revocation of permission to stay or the process of deportation with prior written notification information. Then criminal sanctions for foreigners who commit acts that have been successfully proven to abuse the granting of a Stay Permit that has previously been successfully obtained, then this is successfully regulated in Article 122 of the Immigration Law.